2015
DOI: 10.1155/2015/858907
|View full text |Cite
|
Sign up to set email alerts
|

A Method to Improve Electron Density Measurement of Cone-Beam CT Using Dual Energy Technique

Abstract: Purpose. To develop a dual energy imaging method to improve the accuracy of electron density measurement with a cone-beam CT (CBCT) device. Materials and Methods. The imaging system is the XVI CBCT system on Elekta Synergy linac. Projection data were acquired with the high and low energy X-ray, respectively, to set up a basis material decomposition model. Virtual phantom simulation and phantoms experiments were carried out for quantitative evaluation of the method. Phantoms were also scanned twice with the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…Compared to the reference values provided by the vendor, our method obtained a mean percent error of 0.0 ± 1.8%. The largest uncertainties were observed for the bone inserts, which are known to be a problematic region for correct RED and RSP measurement(Matsufuji et al 1998, Kanematsu et al 2012, Peng et al 2016.Nevertheless, the results for the other inserts compare well to the 2% maximum error observed in the Men et al(Men et al 2015) study. The mean error measured for our RED estimation method was 0.00 ± 0.02 which compares well with Schyns et al(Schyns et al 2017) who observed a mean error of 0.01 ± 0.03.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Compared to the reference values provided by the vendor, our method obtained a mean percent error of 0.0 ± 1.8%. The largest uncertainties were observed for the bone inserts, which are known to be a problematic region for correct RED and RSP measurement(Matsufuji et al 1998, Kanematsu et al 2012, Peng et al 2016.Nevertheless, the results for the other inserts compare well to the 2% maximum error observed in the Men et al(Men et al 2015) study. The mean error measured for our RED estimation method was 0.00 ± 0.02 which compares well with Schyns et al(Schyns et al 2017) who observed a mean error of 0.01 ± 0.03.…”
supporting
confidence: 74%
“…Additionally, RED images were produced by replacing the attenuation coefficient of Al and PMMA by their corresponding RED values in the decomposed projections (Men et al 2015).…”
Section: Vm/red Image Productionmentioning
confidence: 99%
“…The implementation procedure of DE-CBCT imaging for the RED calculation and treatment planning is shown in Fig 2. The detailed steps to calculate the RED could be found in our previous work 35 . The corresponding high and low X-ray projections acquired under the same imaging angle were registered using the Insight…”
Section: D Red Calculation Methodsmentioning
confidence: 99%
“…Previously, we proposed a projection-based (not image-based) dual-energy decomposition 35 to calculate the RED of a head-like CIRS phantom using high-and low-kV CBCT projections. Here, we describe the implementation of a dual-energy imaging and processing method to improve the image quality and accuracy of the dose calculation based on CBCT images in radiotherapy planning based on a Synergy™ (Elekta, Stockholm, Sweden) system.…”
Section: Introductionmentioning
confidence: 99%
“…To increase the benefit of dual-energy imaging, the overlap should be minimized [12]. Previous research on DE imaging has focused on the linear mixing of the low and high energy acquisitions using conventional filtered back-projection (FBP) [13], but no clear benefit has been shown yet. A common alternative to the FBP based algorithms are the iterative reconstruction algorithms.…”
Section: Introductionmentioning
confidence: 99%